Potensi Pengembangan Wakaf Saham Sebagai Objek Wakaf Baru Di Indonesia: Perspektif Hukum Islam - Fauzi, Fahrul (Jurnal Hukum & Pembangunan, 2021)
Share waqf is holding one or more shares owned by wakif in a company that is engaged in a field that is permitted under sharia, the profits of which are used according to the purpose of waqf both for public and private in the framework of worshiping Allah SWT. The regulation of share waqf in Indonesia is still incorporated in the provisions of waqf in general. The existence of this regulation is the result of ijtihad by Indonesian ulama who adjusts to the needs and current social conditions. Shares in Islamic law are categorized as a form of Syirkah. The opinion of the jumhur ulama regarding the use of shares as the object of waqf is permissible, only the Mazhab Hanafi is of the opinion that share waqf is invalid because shares are a movable object. This paper discusses how the concept and model of share waqf, the arrangement and views of positive law and Islamic law on share waqf, as well as the potential and challenges of stock waqf to be developed. The research method used in this paper is a normative legal research method supported by technical qualitative data analysis.